Drinking Water Fluor Levels and The Event of Dental Carries in The Community of Tondo Village Mantikulore District Central Sulawesi - Sapriana Sapriana; Hanum Sasmita; Dedi Mahyudin Syam (Poltekkes Kemenkes Palu, 2023)
According to WHO, the level of fluorine in water that is safe for consumption is 0.7-1.5 ppm. The Indonesian population's prevalence of problems with teeth and mouth is 25.9%. The average Indonesian population has experienced tooth decay as much as 5 teeth per person. Central Sulawesi is a province with the largest dental health problems, namely 75.3% and only 8.2% has received services from dental medical personnel. This study aimed to know the fluorine level of drinking water and the proportion of dental caries in Tondo Village, Mantikulore District, Palu City, Central Sulawesi. This research is descriptive research. The population in this study were people in Tondo Village, Mantikulore District, Palu City, Central Sulawesi. The sample used in this study were part of the community who consumed groundwater (wells) used for drinking and lived in Tondo Village for about 2 years. There were 20 samples of drinking water, and the respondents who had their drinking water samples were also tested for their teeth. Sampling was done by means of non-random sampling, namely by purposive sampling. The results showed that of the 20 respondents, most of the respondents had very low water fluorine levels (95%). The smallest fluorine level was 0.00 mg / l, the highest was 0.40 mg / l, with a median of 0.20 mg / l. or if categorized most (94.7%) had very low fluorine levels, and all respondents experienced dental caries (100%). It is suggested to the public to brush their teeth regularly at least twice a day, that is, after each meal and go to bed at night with fluorine toothpaste.